Interdepartmental Interaction in Realization of Social and Educational Inclusion for Vulnerable Groups - Rubtsov V.V (Moscow State University of Psychology and Education, 2016)
Report on the Meeting of the Russian Federation Government Council for Patronage in Social Sphere at the House of the Government of the Russian Federation, September 28, 2015. S.V. Alyokhina (Moscow State University of Psychology & Education), N.V. Dvoryanchikov (Moscow State Univer- sity of Psychology & Education), E.Yu. Klochko, A.A. Margolis (Moscow State University of Psychology & Educa- tion), G.V. Semya (Moscow State Pedagogical University ), R.V. Chirkina (Moscow State University of Psychology & Education) participated in content discussion and preparation.